Improving institutional platforms for evidence-informed decision-making: getting beyond technical solutions - Jeffrey Mecaskey; Ben Verboom; Marco Liverani; Rhona Mijumbi-Deve; Nasreen S. Jessani (BMC, 2023)
Abstract Purely technical interventions aimed at enhancing evidence-informed decision-making (EIDM) have rarely translated into organizational institutionalization or systems change. A panel of four presentations at the Health Systems Global 2020 conference provides a basis for inference about contextual factors that influence the establishment and sustainability of institutional platforms to support EIDM. These cases include local structures such as citizen panels in Uganda, regional knowledge translation structures such as the West African Health Organization, global multilateral initiatives such as the "One Health" Quadrapartite and regional public health networks in South-East Asia. They point to the importance of political economy as well as technical capability determinants of evidence uptake and utilization at institutional, organizational and individual levels. The cases also lend support to evidence that third-party (broker and intermediary) supportive institutions can facilitate EIDM processes. The involvement of third-party supranational organizations, however, poses challenges in terms of legitimacy and accountability.